2019
DOI: 10.1016/j.carj.2019.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Citation Rate for Original Research Studies in the Canadian Association of Radiologists Journal

Abstract: Objective This study is aimed to identify predictors of citation rate of original research published in the Canadian Association of Radiologists Journal (CARJ). Methods A search of MEDLINE was conducted from January 1, 2000-June 30, 2013 to identify all studies published in the CARJ. Original research studies were included. Reviews, pictorial essays, guidelines, case studies, case series, and original studies with a sample size <10 were excluded. Variables assessed for association with citation rate include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 27 publications
6
12
0
Order By: Relevance
“…In this review, no significant link was found between citation rates of GBM clinical trials and the numbers of authors, centers, countries, and references. A similar finding was reported by other studies [ 2 , 20 ]. However, in the literature, several publications have identified the number of authors as a significant predictor of citation [ 1 , 7 , 15 ].…”
Section: Reviewsupporting
confidence: 93%
See 4 more Smart Citations
“…In this review, no significant link was found between citation rates of GBM clinical trials and the numbers of authors, centers, countries, and references. A similar finding was reported by other studies [ 2 , 20 ]. However, in the literature, several publications have identified the number of authors as a significant predictor of citation [ 1 , 7 , 15 ].…”
Section: Reviewsupporting
confidence: 93%
“…In this analysis, a significant association with the study population was observed in both primary and secondary analysis, implying that the study population was a firm predictor of citation rates in GBM clinical trials. Similar findings relating to the study population were reported by other studies [ 2 , 4 , 6 , 9 , 20 ]. A significant correlation with the trial phase was also seen in both primary and secondary analysis, indicating that being a phase III trial was a solid predictor of citation rates.…”
Section: Reviewsupporting
confidence: 92%
See 3 more Smart Citations